2002
DOI: 10.1093/gerona/57.1.m7
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Vitamin D, Physical Performance, and Disability in Elderly Persons

Abstract: In community-dwelling elderly women, 25(OH)D is related to muscular function and reported disability. Because of the high prevalence of hypovitaminosis D in the elderly population, this association seems to be clinically relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
3
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(87 citation statements)
references
References 37 publications
4
78
3
2
Order By: Relevance
“…A number of studies have found an association between 25-hydroxyvitamin D (25(OH)D) and measures of muscle strength in healthy older people [4][5][6], and vitamin D supplementation decreases the risk of falls [7,8]. Polymorphisms in the vitamin D receptor (VDR) have been shown to influence muscle strength in normal [9,10] and COPD [11] populations.…”
mentioning
confidence: 99%
“…A number of studies have found an association between 25-hydroxyvitamin D (25(OH)D) and measures of muscle strength in healthy older people [4][5][6], and vitamin D supplementation decreases the risk of falls [7,8]. Polymorphisms in the vitamin D receptor (VDR) have been shown to influence muscle strength in normal [9,10] and COPD [11] populations.…”
mentioning
confidence: 99%
“…It has been suggested that higher concentrations of this vitamin may promote physical performance 40,41 , decreasing the risk of mobility limitation 42 . However, vitamin D concentration was not performed in the present study, making it difficult to evaluate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…larının çalışmasında bizim çalışmamıza benzer şe-kilde ZAYT ve vitamin D seviyesi arasında ilişki saptanmamıştır [12]. Ancak vitamin D eksikliği ve denge fonksiyonunu ilişkili bulan çalışmalar da mevcuttur [21][22][23]. Pfeifer ve ark.ları vitamin D eksikliğini dengede bozulma ile ilişkili olduğunu bulmuşlardır [11].…”
Section: Discussionunclassified